Fifteen-Year Follow-Up of a Patient with Acinar Cystic Transformation of the Pancreas and Literature Review - Xiaoyun Wen; Jela Bandovic (Hindawi Limited, 2020)
Acinar cystic transformation (ACT), also known as "acinar cell cystadenoma," is a rare and newly recognized benign pancreatic cystic neoplasm. However, its true malignant potential remains unknown. Here, we report a case of ACT with 15-year follow-up. A 10-year-old female initially presented with abdominal pain and was found to have a cystic lesion in the region of pancreatic head on computed tomography scan. She underwent an exploratory laparotomy, and the intraoperative biopsy of the cyst wall showed a true pancreatic cyst without malignancy. Her symptoms subsequently resolved, and she was placed under close ultrasound surveillance. For the next fifteen years, the patient was asymptomatic without any complications and had a successful pregnancy. Surveillance showed the tumor grew in size from 4.2 cm to 6.2 cm in diameter. In the latest five months, she noted occasional abdominal pain. A pylorus-preserving pancreaticoduodenectomy was performed. The resected cystic lesion was multilocular and lined by a single layer of bland epithelium ranging from nondescript flat/cuboidal epithelium to apparent acinar cells which were strongly positive for trypsin, so the final diagnosis was confirmed to be ACT. The prior biopsy was retrospectively reviewed to reveal similar epithelial lining. To the best of our knowledge, this is the longest period of follow-up for ACT to date. Our findings suggest that ACT is a slow-growing neoplasm without malignant transformation after fifteen years. Therefore, we recommend biopsy for histologic diagnosis followed by close ultrasound surveillance without surgical intervention in asymptomatic or young ACT patients.